A QUASI-EXPERIMENTAL STUDY ON SCAFFOLDING EFL LEARNERS’ ORAL LANGUAGE SKILLS - Hussein, Rewan; Ahmed, Hussein (Humanities Journal of University of Zakho, 2026)
This study examines how scaffolding strategies improve the development of oral language skills, particularly speaking and listening, of Kurdish English as a Foreign Language (EFL) university students. Based on Vygotsky’s sociocultural theory and the notion of the Zone of Proximal Development (ZPD), the current study uses a quasi-experimental design to compare and contrast the outcomes of two groups, a control and an experimental. While the control group received regular instruction, the experimental group was exposed to structured scaffolding-based instruction. Moreover, during a four-month experimental course, 86 students completed IELTS-based pre- and post-tests. The data collected from the tests of both groups were analyzed using a combination of descriptive statistics and Paired–Samples t test. The findings revealed that while both groups showed improvement, the experimental group significantly outperformed the control group in both speaking and listening post-tests. Based on this, the experimental group exhibited statistically significant improvement in speaking (t(84) = 3.87, p <.001) and listening (t(84) = 3.45, p <.01). As such, the findings also affirmed the effectiveness of scaffolding strategies in enhancing oral skills, when applied consistently through gradual release of support, collaborative interaction, and constructive feedback from the teacher. This study contributes to a deeper understanding of how scaffolding supports EFL university students in developing their speaking and listening skill